STATE OF MEASLES, RUBELLA AND MUMPS IN THE SARATOV REGION IN 2001-2013 YEARS - T. N. Buchkova; N. I. Zryachkin; S. A. Khmilevskaya (LLC "Diagnostics and Vaccines", 2015)
The analysis of state reports «On the sanitary-epidemiological situation in Saratov region» for 2001-2013 years. In 2003 noted the maximum increase in the incidence of measles to 2.16 per 100 thousand population. Since 2007 by 2011 in the region of measles cases registered. However in 2012 in the Saratov region recorded four cases of measles adults (index - 0.15 per 100 thousand population) and in 2013 - 52 cases of measles (index - 2.07 per 100 thousand population), of these, 17 cases-importations. In 2010 pronounced decrease was registered rubella (in 6389 times) compared to 2001. In 2011 incidence of rubella is not registered. Incidence rates in 2012 and 2013 were, respectively, 0.2 and 0.04 per 100.000 populations. Since 2002, the incidence of mumps decreased 83-fold (from 6.65 in 2002 to 0,08 in 2012). In 2013 mumps incidence in the region is not registered. Analysis of the state vaccinated against measles, rubella and mumps shows that the region as a whole maintained a consistently high (not less than 95.0%) immunization coverage of children and adults from 18 to 35 years.